THE ADITIONS EFFECT EXTRACT BASIL LEAVE OF POWERWARE PARROT FISH (Oreochromis Niloticus) FRESH - Dwetro, Gilbert Rival; ', Suparmi; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The effect of the addition of basil leaf extract to the durability of fresh tilapia (Oreochromis niloticus) has been done in May 2017. This research aims to determine the effect of addition of basil leaf extract to the durability of fresh tilapia fish. The method used in this research is experimental method that is to preserve fresh tilapia fish with the addition of different basil leaf extract. The design used was non factorial group randomized design (GRD) with 4 treatment levels is without basil leaf extract (T0), 50 ml basil leaf extract solution (T1), 75 ml basil leaf extract solution (T2), basil leaf extract solution 100 Ml (T3), while as the group is the long immersion that is 0 hours, 3 hours, 6 hours and 9 hours. Based on the preservation level, the best value of organoleptic T3 from each treatment is seen from the values of rupa, aroma, and texture are 6.8, 6.9 and 7.1, respectively, with the characteristics of whole shape, no defect, less brilliant color and tight skin, neutral specific type odor, Compact texture, less dense and less elastic and pH value 6.56, TPC value 3.52Cfu and TVB value 15.25 mgN / 100g.Keywords: Tilapia Fish, Quality of Fish, Basil Leaf